2007
DOI: 10.1103/physrevb.76.033401
|View full text |Cite
|
Sign up to set email alerts
|

Physisorption of nucleobases on graphene: Density-functional calculations

Abstract: We report the results of our first-principles investigation on the interaction of the nucleobases adenine (A), cytosine (C), guanine (G), thymine (T), and uracil (U) with graphene, carried out within the density functional theory framework, with additional calculations utilizing Hartree-Fock plus second-order Møller-Plesset perturbation theory. The calculated binding energy of the nucleobases shows the following hierarchy: G > T ≈ C ≈ A > U, with the equilibrium configuration being very similar for all five of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
278
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(316 citation statements)
references
References 22 publications
34
278
3
1
Order By: Relevance
“…For G, we find from the Bader analysis that the CNT possesses an excess charge of −0.08 e and correspondingly a slight depletion of electrons on G by +0.08 e. For A with CNT, −0.05 e were found to have been transferred from the nucleic acid base to the CNT. These results should be compared with our corresponding findings from the interaction of nucleic acid bases with a flat graphene sheet [15], where merely 0.02 e were transferred in the case of G.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…For G, we find from the Bader analysis that the CNT possesses an excess charge of −0.08 e and correspondingly a slight depletion of electrons on G by +0.08 e. For A with CNT, −0.05 e were found to have been transferred from the nucleic acid base to the CNT. These results should be compared with our corresponding findings from the interaction of nucleic acid bases with a flat graphene sheet [15], where merely 0.02 e were transferred in the case of G.…”
Section: Resultsmentioning
confidence: 81%
“…Following a similar procedure employed in our previous study with graphene [15], we started by carrying out the optimization process as follows: (i) an initial force relaxation calculation step to determine the preferred orientation and optimum height of the planar base molecule relative to the surface of the CNT; (ii) a curved slice of the potential energy surface was then explored by translating the relaxed base molecules parallel to the CNT surface covering a surface area 4.26Å in height, 70…”
Section: Methodsmentioning
confidence: 99%
“…Several mechanisms have been discussed, including π-π stacking, electrostatic, van der Waals, and hydrophobic interactions [92]. The main contribution is attributed to π-π bonding, which explains why ssDNA binds more strongly to graphene than dsDNA where the bases are hydrogen bonded and stacked within the helical structure [93,94]. The interaction strengths of the different bases with graphene vary as it depends on the polarizability of the DNA bases [93,95].…”
Section: Detection Methods Based On Dna Adsorptionmentioning
confidence: 99%
“…The interaction strengths of the different bases with graphene vary as it depends on the polarizability of the DNA bases [93,95]. Both theoretical and experimental studies report that guanine binds most strongly to graphene while A, T and C have lower and similar interaction strengths [93,[96][97][98][99][100].…”
Section: Detection Methods Based On Dna Adsorptionmentioning
confidence: 99%
“…31 Previous work has focused on characterization of the adsorption of single nucleotides or nucleosides by atomic force microscopy (AFM), 32 isothermal titration calorimetry, 33 and theoretical calculations. [34][35][36] It was concluded that non-electrostatic interactions dominate the binding, 32 and the purine bases bind more strongly than the pyrimidines. 33,35,36 The adsorption of DNA on carbon nanotubes has also been studied.…”
Section: Introductionmentioning
confidence: 99%